Exploring the geothermal potential of Peut Sagoe volcano using Landsat 8 OLI/TIRS images. (November 2022) - Zaini, Nasrullah; Yanis, Muhammad; Abdullah, Faisal; Van Der Meer, Freek; Aufaristama, Muhammad
Abstract: Thermal infrared remote sensing is an emerging technique to determine thermal anomalies in geothermal and volcanic areas. This study investigates the potential of thermal infrared imaging to observe geothermal prospecting and thermal activity in the Peut Sagoe volcano. The volcano has not been completely studied because it is located in a remote frontier area surrounded by dense rainforest and high terrain conditions. We used operational land imager (OLI)/thermal infrared sensor (TIRS) images of Landsat 8 acquired from 2014 to 2020 to get the actual hydrothermal mineral alteration, vegetation changes (Normalized Difference Vegetation Index; NDVI), and land surface temperature (LST) of the volcanic areas, which correlate with geothermal characteristics, such as fumarole and warm ground that exist on the surface of Peut Sagoe volcano. The combination of band ratios such as 7/5, 5/4, and 6/7 effectively estimates the hydrothermal mineral alteration in the volcanic area, which is dominated by several minerals, such as clay, iron oxide, and OH/H2 O-, SO4 -, and CO-bearing minerals. Result analyses of low NDVI and high LST values are related to the vegetation changes and thermal status of the crater area, the top of the volcano, and the warm ground on the western side of the mountain. These identities demonstrate the geothermal potential of the Peut Sagoe volcano. The LST data of OLI/TIRS images indicate increased thermal activity of the volcano from 22–26°C in 2014 to 30–35°C in 2017. However, the temperature of the volcano relatively decreased to 25°C in 2015 and 2020. In order to reduce the solar effects, the LST data from Landsat were also validated with ASTER data using a combination of night and daytime images. The results show a pattern of high thermal anomalies from 2014 – 2020 in several areas suspected of having geothermal manifestations, such as craters and hot springs, the distribution of these anomalies corresponds to LST in Landsat 8 data. Moreover, NDVI values at the potential geothermal location also reduced in 2014 and 2017 due to an increasing underground volcanic activity. Results revealed that remote sense imagery is an effective approach to identifying the geothermal potential and monitoring the thermal status of volcanos in frontier areas.